Choosing optimal rapid manufacturing process for thin-walled products using expert algorithm - Filip Górski; Wieslaw Kuczko; Radoslaw Wichniarek; Adam Dudziak; Maciej Kowalski; Przemyslaw Zawadzki (Journal of Industrial Engineering and Management (JIEM), 2010)
Choosing right Rapid Prototyping technology is not easy, especially for companies inexperienced with that group of manufacturing techniques. Paper summarizes research focused on creating an algorithm for expert system, helping to choose optimal process and determine its parameters for thin-walled products rapid manufacturing. Research was based upon trial manufacturing of different thin-walled items using various RP technologies. Products were categorized, each category was defined by a set of requirements. Basing on research outcome, main algorithm has been created. Next step was developing detailed algorithms for optimizing particular methods. Implementation of these algorithms brings huge benefit for recipients, including cost reduction, supply time decrease and improvements in information flow.
Keywords: 650; decision process; rapid manufacturing; optimization